Simulation of wastewater dispersion of recycling scrap paper from Muc Son Paper factory to the downstream Chu river - Ngo, Tra Mai; Phan, Thi Thanh Hang (Vietnam Journal of Marine Science and Technology, 2021)
This research simulates and forecasts the area as well as the level of pollution dispersion of Muc Son Paper Factory’s wastewater to the downstream of Chu River under two scenarios: Scenario 1 - wastewater treatment system is broken; treatment efficiency is equal to 0; Scenario 2 - wastewater treatment system is working with its designed capacity. The applied results of the MIKE 11 model show that: the impacted area from the plant’s discharge is 0.2 km upstream and 2 km downstream of the confluence point. The simulation results under Scenario 1 show TSS, BOD5 and COD contents being 18.3–35.7 mg/L, 8.3–17.2 mg/L and 12.2–23.7 mg/L, respectively, negatively affect the water environment downstream of Chu river. The results are then compared with measured data to confirm the reliability of the model. This research is a scientific and practical basis for the Muc Son Paper factory to operate the wastewater treatment system and manage the water quality output to ensure environmental regulations.